EFFECT OF LONG-TERM STARVATION ON BRANCHIAL TISSUE GLYCOLYSIS OF FRESHWATER FISH, TILAPIA MOSSAMBICA (PETERS) - Haranath, V Bhaskara; Bhaskar, M; Rao, M V Chalapathy; Rani, P Shobha; Reddanna, P; Govindappa, S (Indian Journal of Fisheries, 2011)
The activity levels of phosphorylases, aldolase and LDH were significantly suppressed with depleted lactic acid content, indicating decreased glycolysis of the tissue of fish subjected to long term starvation. The suppression of glycolysis was correlated towards the regulation of the tissue glycogenolysis and decreased oxygen uptake of the fish.